Estudio de prefactibilidad para la instalación de una planta productora de un batido nutricional a base de harina de quinua (Chenopodium quinoa Willdenow) y suero de leche en polvo - Sandoval Lovon, Jeanpierre Jesus (2020)
This project shows a prefeasibility study for the installation of a plant that produces a nutritional shake based on quinoa flour and whey powder for people who choose a diet and a healthy lifestyle, destined for the Lima Metropolitan market and having a general objective to determine a technical feasibility, economic-financial, environmental and social. This study arises due to the lifestyle in Lima, the social factors that cause time congestion and consequently a low healthy diet.